CaWO₄@MPSiO₂ nanocomposite: synthesis and characterization - Hubenko, K.; Bespalova, I.; Maksimchuk, P.; Mateychenko, P.; Grynyov, R.; Yefimova, S. (Functional Materials, 2018)
The features of obtaining a nanocomposite consisting of the CaWO₄ core which is a scintillation nanocrystal and a mesoporous SiO₂ shell (CaWO4@MPSiO₂ ) are considered. The results of the investigation of microscopic and optical parameters of CaWO₄@MPSiO₂ nanocomposite are presented. The mesoporous SiO₂ shell applied to the nanocrystal can be used both as a host for the photosensitizer, and set the necessary distance between the donor and the energy acceptor.